2015
DOI: 10.1007/s11920-015-0609-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Video Games on Cognition and Brain Structure: Potential Implications for Neuropsychiatric Disorders

Abstract: Video games are now a ubiquitous form of entertainment that has occasionally attracted negative attention. Video games have also been used to test cognitive function, as therapeutic interventions for neuropsychiatric disorders, and to explore mechanisms of experience-dependent structural brain changes. Here, we review current research on video games published from January 2011 to April 2014 with a focus on studies relating to mental health, cognition, and brain imaging. Overall, there is evidence that specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 81 publications
(96 reference statements)
4
31
0
2
Order By: Relevance
“…One study revealed that surgeons who were also game players were able to complete surgeries more quickly while retaining the necessary precision in the operating room [45]. Another study showed that gameplaying surgeons appeared to work more efficiently, not just faster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study revealed that surgeons who were also game players were able to complete surgeries more quickly while retaining the necessary precision in the operating room [45]. Another study showed that gameplaying surgeons appeared to work more efficiently, not just faster.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that gameplaying surgeons appeared to work more efficiently, not just faster. Video games as learning tools might come considered as adverse effects on children who played games such as "Doom" [45].…”
Section: Discussionmentioning
confidence: 99%
“…5 A WHO survey in 2010 found that 55% of adolescent males and 20% of females reported computer gaming more than 2 hours daily; presumably CHR individuals fall within this general range. 27 The findings on the cognitive effects of casual video games in healthy young adults are very mixed, and while some of them do appear to drive gains in visual processing and visual attentional control, some studies have shown that they are associated with changes in cognitive strategies (eg, Baniqued et al 28 ; see Shams et al 29 for a review). Furthermore, surprisingly few studies have examined the effects of video game exposure on verbal memory in either healthy or cognitively impaired individuals.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…The target of this training varies from circumscribed functional domains, such as attention, to broad multidomain cognition . The video game industry, worth more than £3.9 billion in the United Kingdom in 2014 97 and more than $6.2 billion in the United States in 2012, has developed effective strategies to captivate the player's attention, create and maintain motivation to play over long time periods, and even to tap into brain networks associated with reward and addiction . Certain video games, while not having the explicit aim of improving cognition, seem to have some similar broad effects on cognitive function as specific, targeted brain‐training games with respect to improving reaction time, speed of response, and, in some cases, attention.…”
Section: Nonpharmacological Interventions To Enhance Cognitive Performentioning
confidence: 99%